Effect of antibiotics on cellular stress generated in Shiga toxin-producing Escherichia coli O157:H7 and non-O157 biofilms. Issue 7 (October 2015) - Angel Villegas, Natalia; Baronetti, José; Albesa, Inés; Etcheverría, Analía; Becerra, M. Cecilia; Padola, Nora L.; Paraje, M. Gabriela
Highlights Disturbance in pro-antioxidant balance by antibiotics provoked stress in biofilms. Oxidative stress induced by antibiotics had an effect on the release of Stx. Addition of exogeneous antioxidants was able to modulated Shiga toxin release.